Changing South Korean Water Policy after Political and Economic Liberalisation. Issue 2 (15th March 2017) - Hwang, Jin-Tae
ABSTRACT: This study explores the way in which South Korean water policy has been dynamically (re-)constructed by continuing political contestations among diverse social forces acting in and through the state in the face of political and economic liberalisation. The path-dependency of the state-driven water resource policy under the former authoritarian regime did not disappear even after the democratisation. It was difficult to transform the old authoritarian and hierarchical water governance to the newly democratic and environmentally friendly one because the Ministry of Construction, as a main actor in driving water policy under the authoritarian regimes, did not give up its interest in a dam-based policy orientation, although it did partially accept institutional tools for democratic policy making, such as public hearings and the participation of civil society in the process of establishing the water policy plan. It also showed democratic and environment-friendly gestures using the rhetoric of environmentalism and localisation. Overall, this article emphasises the importance of the path-dependency of the past authoritarian regimes under democratised society to better understand the current democratic regime's policy orientation.